Higher Education and COVID-19: Methodological Adaptation and Online Evaluation at Two Universities in Barcelona - Ortega Ortigoza, Daniel (2021)
Introduction: The temporary suspension of face-to-face teaching activity, as a result of the global pandemic caused by COVID-19, has implied the urgent transformation of the teaching-learning processes in the university context, and an adaptation of programming. Goal: To highlight the consequences generated by COVID-19 and the confinement of university students, and to describe the teaching experiences in two subjects and their respective evaluation strategies in two Catalan universities. Method: Description of the experience in adapting the teaching and assessment of two subjects as a result of the pandemic, which have contributed to the transformation of teaching in the field of higher education, making it more flexible and adapting it to the needs of students in the last semester. Conclusion: The modifications and adaptations in the teaching methodologies and assessment procedures have contributed to the coping with the adverse situation, and the assessment of the teaching-learning processes in a highly complex scenario.